Enhancing sulfide stress cracking resistance of a Cu-bearing high strength low alloyed steel through decreasing austenitizing temperature - Tianyi Zeng; Qingzhan Zhang; Shuzhang Zhang; Yong Zhou; Yinghui Zhao; Xianbo Shi; Wei Yan (Journal of Materials Research and Technology)
To answer a longstanding question towards how the austenitizing temperature affects the sulfide stress cracking (SSC) resistance in high strength low alloyed (HSLA) steels for oil country tubular goods (OCTG), it is necessary to study effects of the austenitizing temperature on martensite microstructure, diffusion and distribution behaviors of hydrogen atoms and SSC resistance. The current work showed that prior austenite grain size (PAGS) greatly increased as the austenitizing temperature was increased from 820 °C to 910 °C, but slightly increased with a further increase to 1000 °C. Similar trend arose in the size and volume fraction of Cr-rich carbides and effective grain size of martensite. The dislocation density was similar after quenching from various austenitizing temperatures, but after tempering it was found to be increased with the increase in austenitizing temperature. Moreover, although dislocations remarkably decreased the effective hydrogen diffusion coefficient (D0), these trapped hydrogen atoms could readily detrap, increasing the apparent hydrogen solubility (Capp). High angle grain boundaries (HAGBs) decreased Capp, indicating their role as obstacles other than as short-circuit diffusion paths for hydrogen diffusion. Compared with coarse Cr-rich carbides, their small counterparts could stably trap more hydrogen atoms. Without sacrificing the strength, the SSC resistance was greatly increased through decreasing the austenitizing temperature, reasons came down to less dislocations, higher HAGBs density, more recrystallized regions and finer Cr-rich carbides.